Dehydroepiandrosterone and dehydroepiandrosterone sulfate levels in combat veterans with or without a history of suicide attempt. (22nd May 2018) - Sher, L.; Flory, J.; Bierer, L.; Makotkine, I.; Yehuda, R.
Abstract : Objective: The goal of this study was to determine whether combat veterans who have made a suicide attempt postdeployment can be distinguished from combat veterans who have never made a suicide attempt based on differences in psychological and biological variables. Methods: Demographic and clinical parameters of suicide attempters and non‐attempters were assessed. Blood samples were assayed for dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS). Results: Suicide attempters had higher Scale for Suicidal Ideation and Montgomery–Åsberg Depression Rating Scale (MADRS)—suicidal thoughts item scores in comparison with non‐attempters. There was a trend toward higher MADRS scores in the suicide attempter group compared with non‐attempters. Suicide attempters had significantly lower levels of DHEA and DHEAS compared with non‐attempters. Scale for Suicidal Ideation scores in all study participants combined negatively correlate with DHEA and DHEAS levels. DHEAS levels negatively correlate with Scale for Suicidal Ideation scores in suicide non‐attempters but not in suicide attempters. DHEA/DHEAS ratios positively correlate with total adolescence aggression scores, total adulthood aggression scores, and total aggression scale scores in suicide attempters but not in suicide non‐attempters. Conclusion: There are psychobiological differences between combat veterans with or without a history of suicidal behaviour.